1981
DOI: 10.1021/bi00508a051
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of the lipid-water interface of model membranes as revealed by lifetime-resolved fluorescence emission spectra

Abstract: We examined the dynamic properties of the lipid-water interface region of model membranes, on the nanosecond time scale, by using the fluorescent probe 2-p-toluidinylnaphthalene-6-sulfonic acid (TNS). In particular, we examined the steady-state emission spectra of TNS as its average lifetime was decreased by oxygen quenching. Under these quenching conditions the centers of gravity (Vcg) of the emission spectra shift ot shorter wavelengths. The lifetime dependence of these shifts reveals the time dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…The time-resolved spectral properties of fluorophores may be easily and reliably obtained from the frequency-domain measurements. The rates of spectral relaxation are in agreement with those estimated previously using the time-resolved method [11,16,23] and phase-sensitive detection of fluorescence [11] for TNS-labeled vesicles. Also, in the case of Patman, the results are in agreement with earlier studies in which the spectral relaxation was examined by phase-sensitive detection of fluorescence [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The time-resolved spectral properties of fluorophores may be easily and reliably obtained from the frequency-domain measurements. The rates of spectral relaxation are in agreement with those estimated previously using the time-resolved method [11,16,23] and phase-sensitive detection of fluorescence [11] for TNS-labeled vesicles. Also, in the case of Patman, the results are in agreement with earlier studies in which the spectral relaxation was examined by phase-sensitive detection of fluorescence [17].…”
Section: Discussionsupporting
confidence: 88%
“…At each wavelength, the phase angle and modulation were measured using approximately ten frequencies. Patmanlabeled and TNS-labeled vesicles were prepared as described previously [17,23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where I (hi) is the intensity at wavelength hi (Lakowicz and Hogen, 1981). Emission spectra were not corrected for instrumental response.…”
Section: Methodsmentioning
confidence: 99%
“…6,16 In addition to perturbing the structure of intramicellar water, the reverse micellar environment can significantly alter its dynamical properties. While a range of measurements have shown that the mobility of water at the lecithin interface is significantly lower than that in bulk water, 12,19,21,36,39,43 the techniques used could not follow the ultrafast motion of water. Hence, these studies do not distinguish water interacting with the interface unless its dynamical response is slowed by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%